Investigating the change in prospective science teachers’ self-efficacy beliefs and the sources of this change during the teaching practice course - Yerdelen, Sundus; Tas, Yasemin; Osmanoglu, Aslihan (Frontiers in Education, 2024)
This study is driven by a dual objective. Firstly, it aims to scrutinize the trajectory of selfefficacy beliefs among prospective science teachers before and after their participation in the Teaching Practicum Course which was conducted for 14 weeks. To accomplish this, 201 senior prospective teachers were stratified into low and high self-efficacy cohorts based on their precourse overall self-efficacy and sub dimensions of self-efficacy (i.e. efficacy for student engagement, instructional strategies, and classroom management) assessments. Subsequently, a mixed between-within-subjects ANOVA was employed to ascertain whether significant differences existed between these groups, utilizing post-course self-efficacy scores. Secondly, this study attempts to explore the factors influencing prospective teachers' selfefficacy beliefs within the scope of self-efficacy sources. To this end, predictor variables such as the number of courses taught by prospective teachers, class sizes, adequacy of school resources, the level of mentorship received, and initial efficacy levels were incorporated, and multiple linear regression analyses were conducted. The findings revealed divergent trajectories in the self-efficacy alterations of low and high self-efficacy groups. Furthermore, it was found that variables such as initial efficacy levels, effective mentoring, and adequacy of school resources significantly explained shifts in self-efficacy. These findings are discussed within the context of related literature.